Studi Eksplorasi Pengaruh Influencer Instagram terhadap Niat dan Keputusan Pembelian Konsumen - Azzahra, Naya Raila; Fitroh, Fitroh (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2025)
This research examines the role of Instagram influencers in shaping consumer purchase intentions and decisions, focusing on various product categories like fashion, beauty, and electronics. Influencer marketing, particularly through micro and macro influencers, has proven to be a powerful strategy in digital marketing due to the emotional engagement influencers foster with their followers. Factors such as the influencer's trustworthiness, the type of content shared (whether informative or entertaining), and the frequency of collaborations play a critical role in shaping consumer preferences and purchase actions. Using a descriptive approach and literature review methodology, the study synthesizes findings from various academic sources published between 2018 and 2024, accessed via Scopus, Web of Science, and Google Scholar. The research highlights that micro-influencers are more effective in building long-term brand loyalty, due to their authentic and personal relationships with their audiences. In contrast, macro-influencers, while effective in increasing brand awareness and influencing short-term purchase decisions, tend to have a more transactional and less emotional impact. The study underscores the importance of emotional connection in influencer marketing and provides valuable insights for marketers looking to leverage Instagram influencers in digital campaigns.